Study of Indices of Proper Housing Model from the Perspective of Residents of Marginal Groups in Mashhad - Rostam saberifar; Hosaein Jangi (تحقیقات کاربردی علوم جغرافیایی)
Experiences acquired in the reorganization of the old structures and buildings of the countrysides and suburbs show that Iran and other countries in the world, have not been successful, because of the inability to build and define a perfect house. This research discusses about the proper indicators related to appropriate houses from the perspective of those who live in such areas. Descriptive and analytic methods have been used. North East outskirt of ​Mashhad was the study ​area because a large population live in this region. The question is: Why people prefer to live in a house with a yard instead of an apartment. In this study,  410 persons were questioned. The collected data through the years 1391 to 1393 were analyzed by SPSS software. The Study shows that age, the year of buying the house, the educational level and the type of house possession affects the suburbs population's views. Therefore, if the governments consider these housing preferences and divide those people into certain subgroups, providing accommodation for them would be more successful. ,